2008
DOI: 10.1158/1078-0432.ccr-08-1257
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccines Targeting Tumor Antigens to B7 Molecules on Antigen-Presenting Cells Induce Protective Antitumor Immunity and Delay Onset of HER-2/Neu-Driven Mammary Carcinoma

Abstract: Purpose: Presentation of tumor antigens by professional antigen-presenting cells (APC) is critical for the induction of tumor-specificT-cell responses. To facilitate targeted delivery of tumor antigens to APC, we generated DNA vaccines that encode secreted fusion proteins consisting of the extracellular domain of CTLA-4 for binding to costimulatory B7 molecules on APC, fused to residues 1 to 222 of human ErbB2 (HER-2) or a corresponding 224 residues fragment of its rat homologue Neu. Experimental Design: Induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
(60 reference statements)
1
14
0
1
Order By: Relevance
“…23,40,41 Given the importance of antibodies in anti-HER-2/neu immunity, potent immunotherapy regimens against HER-2/neu-positive tumors may be designed by combining hN'-neu-shFoxo3 DNA vaccination with passive immunization with anti-p185neu antibodies. Furthermore, other strategies that can elicit both strong antibody and T-cell immune responses to the HER-2/neu antigen, such as the addition of mLAG-3Ig 42 or a TLR-9 43 agonist in the DNA vaccination or the fusion of the extracellular domain of the CTLA-4 to the HER-2/neu, 44 may confer synergistic antitumor effects against HER-2/neu-positive tumors and could be attractive regimens for translation to a clinical setting. In summary, for the first time, we present evidence demonstrating that the silencing of Foxo3 in DCs in vivo by the HER-2/neu DNA vaccine represents an innovative and effective approach to enhance the HER-2/neu antigen-specific CD8 + T-cell immune responses and therapeutic antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…23,40,41 Given the importance of antibodies in anti-HER-2/neu immunity, potent immunotherapy regimens against HER-2/neu-positive tumors may be designed by combining hN'-neu-shFoxo3 DNA vaccination with passive immunization with anti-p185neu antibodies. Furthermore, other strategies that can elicit both strong antibody and T-cell immune responses to the HER-2/neu antigen, such as the addition of mLAG-3Ig 42 or a TLR-9 43 agonist in the DNA vaccination or the fusion of the extracellular domain of the CTLA-4 to the HER-2/neu, 44 may confer synergistic antitumor effects against HER-2/neu-positive tumors and could be attractive regimens for translation to a clinical setting. In summary, for the first time, we present evidence demonstrating that the silencing of Foxo3 in DCs in vivo by the HER-2/neu DNA vaccine represents an innovative and effective approach to enhance the HER-2/neu antigen-specific CD8 + T-cell immune responses and therapeutic antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely due to central tolerance leading to the selective deletion of CTL clones reacting with the immunodominant epitope (45) and the suppressing activity of regulatory immune cells (46). Similar to CTLA-4 -targeted plasmid vaccines (42), scFv CD11c -neu CpG vaccination likely mediates antitumoral activity in BALB-neuT mice through neu-specific antibodies and possibly CD4 + T cells (43). Recently, it was shown that depletion of regulatory T cells enabled neu-specific CTL responses after vaccination of neu-transgenic FVB/N mice with a cellular vaccine expressing neu and granulocytemacrophage colony-stimulating factor (47).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, protein vaccines targeted to DEC205 on DCs improved CD4 + T-cell responses and therefore provided help for DNA vaccines to induce CD8 + T-cell immunity [31][34]. Similar approaches were tested for tumor vaccines using fusion of CTLA-4 or CD28 and tumor antigens to enhance specific immunity to tumor antigens [35][37]. In addition, targeted protein vaccines of tumor antigens are also found to induce potent antitumor immunity [38].…”
Section: Discussionmentioning
confidence: 99%